Spatiotemporal distribution of rural multifunctionality and its influencing factors: a case study of the Liaoning Coastal Economic Belt, China - Chen, Yu; Wang, Jun (Frontiers in Environmental Science, 2025)
Rural multifunctionality (RMF) is a critical component of urban–rural overall planning and sustainable development. In China, rural areas have special functions that cannot be replaced by cities, such as residential carrying, agricultural and non-agricultural production, and ecological conservation. However, few studies have determined the direction of rural development and realized rural regional value from the RMF perspective. In this study, 30 counties in the Liaoning Coastal Economic Zone were taken as the research area, and the years 2000, 2013, and 2023 were selected as the research time nodes. This study constructed the RMF index from the living function, production function, and ecological function and systematically analyzed and depicted the spatiotemporal distribution process of rural functions using trend surface analysis and exploratory spatial data analysis. A geographical detector model was employed to further analyze the influencing factors. The results are as follows: (1) Rural regional agglomeration had obvious characteristics that are undergoing a key transformation from slow to radical. In the spatial dimension, it shows the tendency of high coupling multi-core agglomeration and low coupling dispersion. (2) The degree of coupling coordination indicated a shift from reluctant coordination to good coordination, and the gap across counties was narrowing. (3) The dominating determinants had shifted away from natural resources toward socioeconomic and policy environment factors. This will provide an effective reference for investigating the diversification of rural regional space in Liaoning Province, directing the rational use of rural land and accomplishing coordinated development of rural space.